2016
DOI: 10.18632/oncotarget.11703
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic value of preoperative serum tumor markers in resectable adenosqamous lung carcinoma

Abstract: BackgroundAdenosquamous carcinoma is a rare and aggressive form of lung cancer. The prognostic and predictive value of preoperative serum tumor markers and frequency of EGFR mutations in adenosquamous lung carcinoma are unclear.MethodsWe retrospectively analyzed data and samples collected from 106 radically resected adenosquamous lung carcinoma patients with pathological stage I-IIIA between 2008 and 2013. Correlations between serum tumor marker levels and EGFR mutations as well as survival parameters were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…ENO2 is a key enzyme that catalyzes the dehydration of 2‐phospho‐d‐glycerate to phosphoenolpyruvate in glycolysis and the reverse reaction in gluconeogenesis. It was found as an important prognostic factor in lung and neuroendocrine tumors . Recently, functional studies demonstrated that ENO2 promoted cell growth and glycolysis in acute lymphoblastic leukemia .…”
Section: Discussionmentioning
confidence: 99%
“…ENO2 is a key enzyme that catalyzes the dehydration of 2‐phospho‐d‐glycerate to phosphoenolpyruvate in glycolysis and the reverse reaction in gluconeogenesis. It was found as an important prognostic factor in lung and neuroendocrine tumors . Recently, functional studies demonstrated that ENO2 promoted cell growth and glycolysis in acute lymphoblastic leukemia .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our patient population consisted of an almost equal number of men and women (252 vs. 202). This is important given the sex differences in survival in patients with NSCLC [46].…”
Section: Discussionmentioning
confidence: 99%
“…The cut-offs for serum marker levels were stipulated as follows according to manufacturer's recommendation: CEA 5.0 ng/ml, NSE 15.2 ng/ml, SCCA 1.5 ng/ml, and Cyfra21-1 3.3 ng/ml. EGFR mutations, including EGFR exon 19 deletion (del19) and exon 21 Leu858Arg substitution (L858R), were identified by real-time PCR or DNA sequencing as previously described 15 , 16 . Other EGFR mutations were not tested for.…”
Section: Methodsmentioning
confidence: 99%